(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The revitalisation of traditional market was prioritized by the Indonesian government to protect the unique socio-cultural space. This was achieved through a set of national standards designed to have a more organized and effective infrastructure to meet contemporary requirements. However, only a few have been able to comply with this high standard required. One of the distinct traditional markets without the capacity to fulfil the standards is Mangiran because of the limitations of the area. Therefore, this research investigated an alternative approach to integrate the urban fabric potential into the Mangiran market for the purpose of fulfilling the required standards. The approach was sued to review the national standard in order to have a new perspective and interpretation of traditional markets. The review was further assessed by collecting and analysing primary and secondary data using a qualitative method. The result showed that the integration of urban fabric into Mangiran market was advantageous in challenging the area limitation. This was achieved through the introduction of new types of customers to the market by diversifying the function using both tangible and intangible urban fabric potential.